2019
DOI: 10.1149/2.0211904jes
|View full text |Cite
|
Sign up to set email alerts
|

Current Density Distribution in Electrochemical Cells with Small Cell Heights and Coplanar Thin Electrodes as Used in ec-S/TEM Cell Geometries

Abstract: The electrochemical engineering aspects of high aspect ratio cells, such as those used in in situ electrochemical scanning transmission microscopy (ec-S/TEM) were examined, focusing on aspects that could cause non-uniform current distribution. Having a uniform current distribution across the working electrode is important for any spectroelectrochemical technique in order to provide accurate electrochemical information as well as structural electrolyte-electrode interface information. An analytical model was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…168 Unocic et al reported that it is important to have a well-defined electrode geometry and microfluidic conditions, and ensure that the WE is thin (<50 nm) and highly conductive to ensure a uniform current density distribution for quantitative electrochemical measurements. 169,170 One may notice that the potentials in Figure 5C are presented against a Pt pseudo RE, relying on the metastable redox couple of PtO x /Pt. Given that the position of the characteristic Pt {110} is often located at ∼0.1 V vs RHE, we estimate the potential difference between the Pt pseudo-RE and SHE to be about 0.8 V so that an electrochemist's mind can be easily "calibrated" to the commonly used RHE scale.…”
Section: Scanning and Transmission Electron Microscopy (Stem)mentioning
confidence: 99%
See 1 more Smart Citation
“…168 Unocic et al reported that it is important to have a well-defined electrode geometry and microfluidic conditions, and ensure that the WE is thin (<50 nm) and highly conductive to ensure a uniform current density distribution for quantitative electrochemical measurements. 169,170 One may notice that the potentials in Figure 5C are presented against a Pt pseudo RE, relying on the metastable redox couple of PtO x /Pt. Given that the position of the characteristic Pt {110} is often located at ∼0.1 V vs RHE, we estimate the potential difference between the Pt pseudo-RE and SHE to be about 0.8 V so that an electrochemist's mind can be easily "calibrated" to the commonly used RHE scale.…”
Section: Scanning and Transmission Electron Microscopy (Stem)mentioning
confidence: 99%
“…Zaluzec showed that the electron beam has a significant impact on the open circuit potential (OCP) of the WE in pure H 2 O due to capacitive charging of electrode by the beam but a negligible effect in 1 mM H 2 SO 4 with sufficient ions to rapidly reach charge equilibrium, indicating that the electrochemical signals should be closely monitored when the beam is turned on . Unocic et al reported that it is important to have a well-defined electrode geometry and microfluidic conditions, and ensure that the WE is thin (<50 nm) and highly conductive to ensure a uniform current density distribution for quantitative electrochemical measurements. , One may notice that the potentials in Figure C are presented against a Pt pseudo RE, relying on the metastable redox couple of PtO x /Pt. Given that the position of the characteristic Pt {110} is often located at ∼0.1 V vs RHE, we estimate the potential difference between the Pt pseudo-RE and SHE to be about 0.8 V so that an electrochemist’s mind can be easily “calibrated” to the commonly used RHE scale.…”
Section: Scanning and Transmission Electron Microscopy (Stem)mentioning
confidence: 99%
“…Oxygen plasma, for example, is known to increase hydrophilicity on silicon and its compounds and is commonly used to improve water fluidity and decrease the possibility of void formation in microchannels for many in situ experiments. On the other side, its effect on PMMA seems to go in the opposite direction, and it has been used to increase hydrophobicity in combination with the increase in surface roughness as well [79,80].…”
Section: The Hydrophobic Coating Of Surfacesmentioning
confidence: 99%
“…In CO 2 ERR, the faradaic efficiency must be considered since it represents the efficiency with which charges (electrons) are transported in a system, promoting an electrochemical reaction. On the other hand, the current density, which is defined as the rate of charge passed across a specified cross-section unit area per unit time [42], is affected by the conductivity and thickness of the thin film on the electrode [43]. The main problem associated with this technology is finding a catalytic system that can efficiently convert CO 2 to the desired value-added product at a low energy requirement.…”
Section: Introductionmentioning
confidence: 99%